A New Model of Ultracapacitors Based on Fractal Fundamentals - Xiaodong Zhang; Yi Sun; Jia Song; Aijun Wu; Xiaoyan Cui (Journal of Applied Mathematics)
An intuitive model is proposed in this paper to describe the electrical behavior of certain ultracapacitors. The model is based on a simple expression that can be fully characterized by five real numbers. In this paper, the measured impedances of three ultracapacitors as a function of frequency are compared to model results. There is good agreement between the model and measurements. Results presented in a previous study are also reviewed and the paper demonstrates that those results are also consistent with the newly described model.